S.M.A.R.T Business Role in Supporting Marketing Strategies among Telecommunication Organizations Injordan - Yanal Mahmoud Kilani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current study aimed at examining the role of S.M.A.R.T business goals including (specific, measurable, assignable, realistic and time-related) in supporting marketing strategies within telecommunication organizations in Jordan. In order to realize the aim, quantitative approach was adopted through distributing an online questionnaire on a sample of (134) individuals within telecommunication industry in Jordan. Results of study indicated that employing the aspects of S.M.A.R.T business goals and apply them on the marketing strategies helped in creating the so-called 'smart marketing', this type of marketing suited the current era of online and internet marketing and managed to increase the suitability and performance of marketing activities. In addition to that, among variables of S.M.A.R.T business goals, it was seen that all variables were influential; the highest variables in influence appeared to be for the benefit of realistic and timely strategies, meaning that realistic goals and having a timely deadline for achieving each goal is very impactful in presenting an efficient marketing strategy. Study recommended the need for marketing strategies not to be general, that is, not only (increasing followers of social media sites), but the mechanism that will achieve the goals of the strategy must be supported in a smart and effective way.